Discovery of a Carbamoyl Phosphate Synthetase 1–Deficient HCC Subtype With Therapeutic Potential Through Integrative Genomic and Experimental Analysis. Issue 6 (11th October 2021) - Wu, Tong; Luo, Guijuan; Lian, Qiuyu; Sui, Chengjun; Tang, Jing; Zhu, Yanjing; Zheng, Bo; Li, Zhixuan; Zhang, Yani; Zhang, Yangqianwen; Bao, Jinxia; Hu, Ji; et al.
Abstract : Background and Aims: Metabolic reprogramming plays an important role in tumorigenesis. However, the metabolic types of different tumors are diverse and lack in‐depth study. Here, through analysis of big databases and clinical samples, we identified a carbamoyl phosphate synthetase 1 (CPS1)‐deficient hepatocellular carcinoma (HCC) subtype, explored tumorigenesis mechanism of this HCC subtype, and aimed to investigate metabolic reprogramming as a target for HCC prevention. Approach and Results: A pan‐cancer study involving differentially expressed metabolic genes of 7, 764 tumor samples in 16 cancer types provided by The Cancer Genome Atlas (TCGA) demonstrated that urea cycle (UC) was liver‐specific and was down‐regulated in HCC. A large‐scale gene expression data analysis including 2, 596 HCC cases in 7 HCC cohorts from Database of HCC Expression Atlas and 17, 444 HCC cases from in‐house hepatectomy cohort identified a specific CPS1‐deficent HCC subtype with poor clinical prognosis. In vitro and in vivo validation confirmed the crucial role of CPS1 in HCC. Liquid chromatography–mass spectrometry assay and Seahorse analysis revealed that UC disorder (UCD) led to the deceleration of the tricarboxylic acid cycle, whereas excess ammonia caused by CPS1 deficiency activated fatty acid oxidation (FAO) through phosphorylated adenosine monophosphate–activated protein kinase. Mechanistically, FAO provided sufficient ATP for cell proliferation and enhanced chemoresistance of HCC cells by activating forkhead box protein M1. Subcutaneous xenograft tumor models and patient‐derived organoids were employed to identify that blocking FAO by etomoxir may provide therapeutic benefit to HCC patients with CPS1 deficiency. Conclusions: In conclusion, our results prove a direct link between UCD and cancer stemness in HCC, define a CPS1‐deficient HCC subtype through big‐data mining, and provide insights for therapeutics for this type of HCC through targeting FAO.